Toll-Like Receptor 2 is Involved in Abnormal Pregnancy in Mice Infected with Toxoplasma gondii During Late Pregnancy - Ikeda, Rina; Ushio, Nanako; Abdou, Ahmed M.; Furuoka, Hidefumi; Nishikawa, Yoshifumi (Frontiers in Microbiology, 2021)
Infection with Toxoplasma gondii during pregnancy causes failure of pregnancy maintenance, resulting in fetal death, abortion, stillbirth, or premature birth, but the mechanism of disease onset remains unclear. Although Toll-like receptor 2 (TLR2) is expressed on antigen-presenting cells and trophoblasts, the role of TLR2 in T. gondii infection during pregnancy is unknown. In this study, we investigated the role of TLR2 in congenital toxoplasmosis using TLR2-deficient (TLR2−/−) mice. Toxoplasma gondii infection on gestational day 12.5 (Gd12.5) induced more abnormal pregnancy, including premature birth and stillbirth, in wild-type mice than in TLR2−/− mice. Multiple calcifications were observed in the placentas of the infected wild-type mice. At Gd18.5 (6 days postinfection), the parasite numbers in the placenta and uterus and the histological changes did not differ significantly between the wild-type and TLR2−/− mice. However, T. gondii infection reduced the mRNA expression of interleukin-12p40 (IL-12p40) and increased IL-4 and IL-10 mRNAs in the placentas of the wild-type mice. In contrast, the placentas of the TLR2−/− mice showed no changes in the expression of these cytokines, including IL-6 and tumor necrosis factor α, in response to T. gondii infection. Serum interferon-γ levels were significantly lower in the infected TLR2−/− mice than in the infected wild-type mice on Gd18.5. Thus, the TLR2−/− mice were less susceptible to the induction of immune responses by T. gondii infection during late pregnancy. Therefore, TLR2 signaling may play a role in the development of disease states during pregnancy, specifically placental hypofunction.